Kinetics of catalytic biomass pyrolysis using Ni-based functional materials - Yang, Hang; Ji, Guozhao; Clough, Peter T. (Elsevier, 2019)
The pyrolysis behaviors of three types of biomass (cellulose, sawdust and straw) in three cases (no catalyst, Ni-CaO-Ca2SiO4 and Ni-Ca2SiO4) were investigated by non-isothermal thermogravimetric analysis. The non-isothermal pyrolysis was implemented with four different heating rates: 20, 30, 40 and 50 °C/min and the yield rates of the produced gases were measured by TG-MS. For kinetic analysis, the activation energy was obtained using four isoconversional analysis methods (Flynn-Wall-Ozawa (FWO) method, Kissinger-Akahira-Sunose (KAS) method, Starink method, and the Miura distributed activation energy model (DAEM)). Ni-CaO-Ca2SiO4 and Ni-Ca2SiO4 was found to intensify the decomposition of biomass to produce more H2 and CO. The correlation R2, of all fitting lines in all cases, was above 0.9 which demonstrated that FWO, KAS, Starink methods and DAEM were suitable for calculating the activation energy of the biomass catalytic pyrolysis. Ni-CaO-Ca2SiO4 showed the obvious catalytic effects in the decrease of activation energy of biomass pyrolysis to produce additional H2 and CO from the breakage of light organic molecules.
Keywords: Biomass; Pyrolysis; Catalytic; Kinetic analysis; Functional materials